A novel pre-deposition assisted strategy for inkjet printing graphene-based flexible pressure sensor with enhanced performance. (30th August 2022) - Sun, Jiawei; Sun, Yunfei; Jia, Haiyang; Bi, Hengchang; Chen, Lixiang; Que, Miaoling; Xiong, Yuwei; Han, Longxiang; Sun, Litao
Abstract: Inkjet printing of graphene-based materials represents a highly promising deposition method, as benefits of its flexibility for graphical printing and simple operation process. However, the huge challenge associated with inkjet printing of graphene-based inks is to overcome the coffee ring effect, which results in ununiformity of the printed pattern. In this paper, we innovatively demonstrate a novel and facile pre-deposition assisted strategy for inkjet printing of graphene ink. By simply pre-depositing an ethanol layer, a series of procedures including homogenization, solvent exchange, post-stretching, and air drying would take place, leading to uniform deposition of graphene nanosheets with a denser structure. The as-printed pattern was proved to have a flatter surface. Subsequently, the approach was applied to construct an interdigital capacitance pressure sensor with a polyethylene terephthalate (PET) substrate. Such sensors showed high sensitivity (the relative capacitance change reached 33 under 10000 Pa), low detection limits (clearly perceive the weight of 0.1 g), and excellent stability. Notably, it exhibited negligible thermal hysteresis and decreased performance compared with the sensor fabricated by direct printing, which stems from its compact structure and lower air content. The method we proposed opens up opportunities for practical applications of inkjet printing low-cost graphene-based electronic devices with desirable performance. Graphical abstract: Image 1 Highlights: Proposing a novel strategy for inkjet printing graphene-based pressure sensor that can alleviate the coffee ring effect. Uniform surface reduces the randomness of the topography, making the properties of the printing devices more controllable. Densifying the printed lines, thus improving the conductivity of the electrodes. Facile operation and environmentally-friendly processes make the strategy more practical. Enhancing the sensitivity and stability, decreasing the thermal hysteresis of the as-printed graphene-based sensors.